2019
DOI: 10.1038/s41598-019-41917-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of systemic vascular risk factors on the choriocapillaris using optical coherence tomography angiography in patients with systemic hypertension

Abstract: We investigated the characteristics of the choriocapillaris flow voids using optical coherence tomography angiography (OCTA) in 85 patients (164 eyes) with hypertension (mean ± SD age, 56 ± 11 years; 45% women; 20% poorly controlled BP; 16% diabetes) who are without ocular diseases and determined possible correlations with systemic vascular risk factors. Data on 24-hour ambulatory blood pressure (BP), serum creatinine, and urine microalbumin/creatinine ratio (MCR) were collected. Estimated glomerular filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 58 publications
3
58
0
Order By: Relevance
“…Our results support the hypothesis that microvascular damage is present in patients with hypertensive crisis and correspond with studies in patients with chronic systemic hypertension in whom reduction of retinal capillary density has previously been shown. [23][24][25][26][27] Chua et al 23 found significant correlations between blood pressure and glomerular filtration rate, on one hand, and retinal capillary density on OCTA, on the other hand, in 77 subjects with chronic hypertension. They hypothesized that arteriolar narrowing due to atherosclerosis could lead to a loss of the retinal vascular autoregulation and capillary rarefaction.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the hypothesis that microvascular damage is present in patients with hypertensive crisis and correspond with studies in patients with chronic systemic hypertension in whom reduction of retinal capillary density has previously been shown. [23][24][25][26][27] Chua et al 23 found significant correlations between blood pressure and glomerular filtration rate, on one hand, and retinal capillary density on OCTA, on the other hand, in 77 subjects with chronic hypertension. They hypothesized that arteriolar narrowing due to atherosclerosis could lead to a loss of the retinal vascular autoregulation and capillary rarefaction.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we adjusted the possible confounding effects of age, gender, race, and the presence of diabetes, and systemic blood pressure levels during multivariate analysis and excluded possible confounding factors, such as glaucoma, vascular or nonvascular retinopathies, age-related macular degeneration. [24,25,32] Our present study has a few limitations. First, even though there was reduced retinal VD in those with AD and MCI using OCTA, this was only a cross-sectional study.…”
Section: Foveal Avascular Zone Areamentioning
confidence: 90%
“…We excluded participants from the analysis if the OCTA images from both eyes were of poor quality (poor signal strength index < 7, signi cant motion artefacts visible as irregular vessel patterns on the en face angiogram, local weak signal caused by artefacts such as oaters, misalignment or incorrect segmentation). [24,25] A randomly selected eye was analyzed for each participant since measurements of both eyes were highly correlated.…”
Section: Optical Coherence Tomography Angiographymentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was supported by a recent OCTA study of choriocapillaris perfusion in patients with wellcontrolled vs. poorly controlled hypertension. Patients with well-controlled hypertension (and lower systolic blood pressure) had small increases in choriocapillary flow voids compared to patients with poorly controlled hypertension (and higher systolic blood pressure) (Chua et al 2019). Similarly, in a population of normotensive patients, increasing blood pressure was associated with increased choroidal perfusion (Polak et al 2003).…”
Section: Hypertensionmentioning
confidence: 97%